CLT construction without weather protection requires extensive moisture control. (July 2021) - Olsson, Lars
This study examines how cross-laminated timber (CLT) constructions, including joints, connections and attachment points, are affected by precipitation during construction. The case studies are based on moisture content measurements and material sampling as well as microbiological analysis during the structure's construction stage. The study does not include remediation control. The field measurements show microbiological growth in all buildings and almost all floor structures that were investigated. Of a total of 200 measuring points analysed, half had mould growth and around a third had moderate or extensive growth. The moisture content measurements for one of the locations with the largest percentage of elevated or high moisture content was at the top of the floor structure in the bottom gap between timbers in the CLT top layer. This is one example of several materials or construction components where there is limited possibility of dry out. Based on the outcome, it would appear difficult, or impossible, to avoid the appearance of microbial growth during construction with CLT without weather protection. Previous studies indicate that microbiological analysis of CLT is extremely rare in both laboratory and field studies, which implies that there are obvious shortcomings in the scientific work. The fact that mould growth is often invisible needs to be disseminated, especially in practical studies. However, there seems to be a good level of awareness in the literature that theoretical studies often conduct mould growth risk evaluations. There do not appear to be any moisture safety assembly methods or solutions for CLT construction that do not have weather protection or a declaration of the critical moisture conditions for CLT products.